Figurative Language And Lecturing In ELT - Tiara Widyaiswara; Ali Nuke Affandy; Zeppyca Almayda Dwi Sahputri (Universitas PGRI Madiun, 2025)
This study aims to identify the types of figurative language used by lecturers in teaching English, determine the most frequently used types, and understand the purpose behind their use. The subjects of the study were English lecturers who taught the second semester Speaking course and the fourth semester TOEFL Preparation class. Data analyzed using qualitative content analysis through , coding, thematic analysis, interpretation, and validation with triangulation were collected through classroom observation and semi-structured interview. The findings of the study indicate that lecturers use various types of figurative language, including Metaphor, Personification, Metonymy, Antonomasia, Hypalas, Irony, Satire, and Antiphrasis. Metaphor as the most dominant, because it effectively conveys abstract ideas in an imaginative way. Less frequent types such as Antonomasia and Hypalase appear situationally. The results of the study indicate that the main purpose of lecturers using figurative language in English learning teaching is to improve students' understanding and provide motivation to students. This study concludes that figurative language plays an important role in teaching English. Future researcher should suggest that lecturers integrate the use of figurative language consciously into their teaching strategies and further research can involve more lecturers and institutions to broaden understanding of the impact of the use of figurative language on student learning outcomes.